Air Pollution by Fraction Particulate Matters PM10, PM2.5 in the Site of Algiers Centers - Yahiaoui, F.; Benrachedi, K.; Belamri, M. (Asian Journal of Chemistry, 2011)
This article concerns the quality of the air in the urban site of Algiers centre. A sampler with low air flow was used for the collection of the samples on the level of this site characterized by the presence of a strong density of circulation of cars. The mass of the ambient particles is a complex mixture which strongly depends on the characteristics of the sources and their sizes according to whether they are "fine" particles or "large" particles. The sampling procedures of the suspended particles in the air multiple and are varied among them, the PM10 and PM2.5 which are taken using a sampler of the type Gent sampler. The analysis of the collected filters was carried out by X-ray fluorescence spectrometry. Heavy metals were proportioned by this technique showing in obviousness the existence of air pollution due mainly to the human activity.